The gifts of Odin: the violaceous amethyst - Lennon-Ritchie, Aoife (Department of English Language and Literature, 2014)
The Gifts of Odin: The Violaceous Amethyst, follows the Miller family as they battle tarantula fish, learn secrets from trees, and go up against a conniving, double-crossing, espresso-drinking villain.